Effect of exercise on lipolytic sensitivity in endurance-trained athletes - Klein, S.; Coyle, E. F.; Wolfe, R. R. (Journal of Applied Physiology)
Studies performed in vitro suggest that an acute bout of exercise increases the lipolytic response to [beta]-adrenergic stimulation. We evaluated the effect of exercise on lipolytic sensitivity in vivo in five endurance-trained athletes. The rate of appearance (Ra) of glycerol in plasma, an index of whole-body lipolysis, was determined during 60 min of epinephrine infusion (0.015 [mu]g.kg-1.min-1) on two occasions: (1) at basal resting conditions and (2) 90 min after completing 1 h of high-intensity (70% VO2) cycle ergometer exercise. Total glycerol Ra during epinephrine infusion in the basal state (352+/-35 [mu]mol.kg-1.60 min-1) was not significantly different from the value obtained after high-intensity exercise (439+/-58 [mu]mol.kg-1.60 min-1). However, the increase in glycerol Ra above baseline during epinephrine infusion was lower after (30+/-16 [mu]mol.kg-1.60 min-1) than before (148 +/- 28 [mu]mol.kg-1.60 min-1) exercise because of the high post exercise baseline value (P < 0.05). Mean plasma FFA concentration was lower during exercise than during epinephrine infusion despite a greater rate of lipolysis during exercise. The slope of change in plasma FFA with respect to glycerol Ra was lower during exercise (0.0171+/-0.006) than during epinephrine infusion (0.0835+/-0.018) (P < 0.05). We conclude that a single bout of intense exercise does not increase in vivo lipolytic sensitivity to [beta]-adrenergic stimulation in endurance-trained athletes. In addition, plasma FFA concentration represents the balance between plasma FFA inflow and tissue uptake and cannot be used as an index of lipolytic activity during certain physiological conditions, such as exercise.